1999
DOI: 10.1128/mcb.19.3.1821
|View full text |Cite
|
Sign up to set email alerts
|

Smad3-Smad4 and AP-1 Complexes Synergize in Transcriptional Activation of the c-Jun Promoter by Transforming Growth Factor β

Abstract: Transcriptional regulation by transforming growth factor ␤ (TGF-␤) is a complex process which is likely to involve cross talk between different DNA responsive elements and transcription factors to achieve maximal promoter activation and specificity. Here, we describe a concurrent requirement for two discrete responsive elements in the regulation of the c-Jun promoter, one a binding site for a Smad3-Smad4 complex and the other an AP-1 binding site. The two elements are located 120 bp apart in the proximal c-Jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
209
1
7

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 257 publications
(231 citation statements)
references
References 63 publications
14
209
1
7
Order By: Relevance
“…Following the discovery of Smads as early transducing molecules downstream of the TGF-b receptors, it has been shown that activation of both c-jun and junB promoters by TGF-b involves Smad-dependent mechanisms (Jonk et al, 1998;Wong et al, 1999). These results are consistent with the respective time courses of activation of Smad and Jun proteins by TGF-b.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…Following the discovery of Smads as early transducing molecules downstream of the TGF-b receptors, it has been shown that activation of both c-jun and junB promoters by TGF-b involves Smad-dependent mechanisms (Jonk et al, 1998;Wong et al, 1999). These results are consistent with the respective time courses of activation of Smad and Jun proteins by TGF-b.…”
Section: Introductionsupporting
confidence: 78%
“…It has been shown previously that induction of c-Jun and JunB components of the AP-1 family of transcription factors by TGF-b occurs downstream of the initial Smad cascade, as Smad-speci®c cis-elements are required for TGF-b-dependent activation of both c-jun and junB promoters (Jonk et al, 1998;Wong et al, 1999). In this report, we have evidenced that secondary jun expression downstream of Smad signaling functions as a mechanism of suppression of Smad-speci®c gene transactivation.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Two days post-transfection, cells were harvested, and His 6 -SUMO conjugates were purified as described (Rodriguez et al 1999) and analyzed using anti-Myc (Santa Cruz Biotechnologies), anti-HA (Abcam), or anti-phosphoSmad1 (Cell Signaling) antibodies. Cell fractionations were performed as described (Wong et al 1999;Pierreux et al 2000). Cells were treated with Leptomycin B (LMB) at a final concentration of 20 ng/mL for 2 h before harvesting.…”
Section: Sumo Assaysmentioning
confidence: 99%
“…The affinity of the Smad3 MH1 domain for the SBE is relatively low, with a Kd of about 10 -7 M (Shi, Wang et al 1998 For example, Smad3 physically interacts with a variety of transcription factors such as AP-1, transcription factor microE3 (TFE3) and hepatocyte nuclear factor 4 (HNF-4), each in specific situations (Hua, Liu et al 1998;Wong, Rougier-Chapman et al 1999). Cooperative binding of Smad3/4 and AP-1 to their recognition sites synergistically activates transcription of TGF-β responsive genes such as collagenase I (Qing, Zhang et al 2000).…”
Section: Smad-mediated Tgf-β Signalingmentioning
confidence: 99%